2013
DOI: 10.1038/nn.3536
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical origins of human and monkey neocortical interneurons

Abstract: Cortical GABAergic inhibitory interneurons have crucial roles in the development and function of the cerebral cortex. In rodents, nearly all neocortical interneurons are generated from the subcortical ganglionic eminences. In humans and nonhuman primates, however, the developmental origin of neocortical GABAergic interneurons remains unclear. Here we show that the expression patterns of several key transcription factors in the developing primate telencephalon are very similar to those in rodents, delineating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
310
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(358 citation statements)
references
References 50 publications
38
310
4
Order By: Relevance
“…These cells often exhibited bipolar or bitufted morphology and coexpressed CR and VIP (Fig. 4E-J), consistent with CGE/LGE origins (Xu et al 2004;Fogarty et al 2007;Miyoshi et al 2010;DeFelipe et al 2013;Ma et al 2013;Dzaja et al 2014;Hladnik et al 2014). …”
Section: Secretagogin Expression In Human Neocortex Is Developmentallsupporting
confidence: 63%
See 2 more Smart Citations
“…These cells often exhibited bipolar or bitufted morphology and coexpressed CR and VIP (Fig. 4E-J), consistent with CGE/LGE origins (Xu et al 2004;Fogarty et al 2007;Miyoshi et al 2010;DeFelipe et al 2013;Ma et al 2013;Dzaja et al 2014;Hladnik et al 2014). …”
Section: Secretagogin Expression In Human Neocortex Is Developmentallsupporting
confidence: 63%
“…For example, interneurons expressing tyrosine hydroxylase appear to be particularly abundant in deep layers of human neocortex relative to other mammalian species (Defelipe 2011). Variation in GABAergic neuron subtype proportions between human and mouse neocortex has also been attributed to species' differences in the neuroanatomical origins of these cells (Letinic et al 2002;Jakovcevski et al 2011;Yu and Zecevic 2011;Radonjic et al 2014a), although this interpretation is not universally accepted (Hansen et al 2013;Ma et al 2013). Our finding of molecular differences in SCGN activity between humans and mice provides further support for efforts to clarify species' differences among subpopulations of GABAergic neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human GE, COUP-TFII is expressed in a gradient manner with a small increase in the CGE at gestational week 15 (33,34). In the human cortex, it is shown that the COUP-TFII expression is abundant in the caudal cortex and moderate in the rostral cortex at gestational weeks 15-22 (33), which are reminiscent of the expression patterns in the mouse cortex at E13.5 shown in this study.…”
Section: Coup-tfii Expression In the Poa And In Poa-derived Gabaergicsupporting
confidence: 76%
“…In the human cortex, it is shown that the COUP-TFII expression is abundant in the caudal cortex and moderate in the rostral cortex at gestational weeks 15-22 (33), which are reminiscent of the expression patterns in the mouse cortex at E13.5 shown in this study. Unfortunately, the COUP-TFII expression in the POa has not yet been examined in the developing human brain; however, a large population in the caudal MGE has been reported to coexpress COUP-TFII and Nkx2.1 (34), similar to the POa2 in the mouse brain shown in the present study. Indeed, it would be worth investigating whether the CMS is present in the developing human brain using double immunohistochemistry for COUP-TFII and Lhx6.…”
Section: Coup-tfii Expression In the Poa And In Poa-derived Gabaergicsupporting
confidence: 59%